DISTANCE EDUCATION EXPERIENCES OF SECONDARY SCHOOL MATH TEACHERS DURING THE PANDEMIC: A NARRATIVE STUDY - Sengil Akar, Seyma; Kurtoglu Erden, Meltem (Turkish Online Journal of Distance Education, 2021)
All schools in Turkey have quickly entered into the process of distance education because of the Covid-19 outbreak. In this process, mathematics teachers have become an associate of this process to teach math lessons at a distance. The subject of the current study is the experiences of teachers in this process of distance teaching of math, which is a compulsory subject in all secondary schools. The participants of the current study designed as a narrative study are 15 math teachers experienced on the subject. As a result of the study, a total of five super-themes emerged. The first super-theme includes codes related to the general structure of the math course. The second super-theme is theme of hardware and Web 2.0 tools. This sub-theme includes codes related to their experiences of EBA TV, EBA Internet and other alternative tools of distance education. The third sub-theme is the Socio Cultural super theme. This theme is consisted of sub-codes including political issues, state of the student, state of the parent and socio-economic situations. The fourth sub-theme includes the codes related to psychological states arising from the extraordinary situation emerging in the pandemic (period of pandemic, cyber bullying, emotional links). The fifth sub-theme is related to the readiness of teachers.
Keywords: Pandemic; Pandemic; Covid 19; math teachers; narrative study; Pandemic; Covid 19; math teachers; narrative study; Covid-19; Math Teachers; 4. Education